2001
DOI: 10.1029/2000gl012711
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of OH, H2SO4, and MSA at the South Pole during ISCAT

Abstract: The first measurements of OH, H2SO4, and MSA performed at the South Pole as part of the Investigation of Sulfur Chemistry in the Antarctic Troposphere (ISCAT) study are presented. OH concentrations were found to be quite elevated for such a dry environment, with average values of 2x106 molecule cm−3. Model simulations suggest that much of the observed OH is a result of unexpectedly high NO concentrations. Concentrations of H2SO4 and MSA were generally low with average values of 2.5x105 and 1x105 molecule cm−3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
112
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(122 citation statements)
references
References 10 publications
8
112
2
Order By: Relevance
“…[27,28] For data obtained in 2000 at the South Pole, model predictions of OH were accurate only in a certain range of NO levels. [4,27] For data obtained at Summit, the discrepancy between model and measured values was found to depend strongly on meteorology: [6] when the wind was light (,6 m s À1 ) the measured value was twice the calculated values, whereas in high wind (.6 m s À1 ) and blowing snow the measured value was an order of magnitude higher than the calculated value. [6] Thus, the model calculations that have used only photochemical reactions have underestimated the level of OH in all cases.…”
Section: Unknown Sources Of Oh Formationmentioning
confidence: 99%
See 3 more Smart Citations
“…[27,28] For data obtained in 2000 at the South Pole, model predictions of OH were accurate only in a certain range of NO levels. [4,27] For data obtained at Summit, the discrepancy between model and measured values was found to depend strongly on meteorology: [6] when the wind was light (,6 m s À1 ) the measured value was twice the calculated values, whereas in high wind (.6 m s À1 ) and blowing snow the measured value was an order of magnitude higher than the calculated value. [6] Thus, the model calculations that have used only photochemical reactions have underestimated the level of OH in all cases.…”
Section: Unknown Sources Of Oh Formationmentioning
confidence: 99%
“…Hydroxyl and superoxide radicals as well as atmospheric nitrogen oxides, carbon monoxide, methane, and hydrogen also participate in radical reaction cycles. Chemical ionisation mass-spectrometry [8] South Pole, ISCAT expedition (Investigation of Sulfur Chemistry in the Antarctic Troposphere), November1998-January 1999 2 Â 10 6 cm À3 Chemical ionisation mass-spectrometry [4] Summit (72 834 0 N, 38 829 0 W, 3250 m ASL), Greenland, 2003 6.4 Â 10 6 cm À3 Chemical ionisation mass-spectrometry [6] Halley Laser-induced fluorescence method [7] Bromine compounds, however, are considered separately because they are very effective ozone depletion catalysts. But the mechanism of bromine release to the gas phase is not fully understood, nor has it been physically interpreted yet.…”
Section: Unknown Sources Of Oh Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, hydroxyl concentrations in Polar Regions have traditionally been expected to be much lower. However, Mauldin et al (2004) reported typical OH concentrations of (2.5-3.5) Â 10 6 molecules cm À3 above the snow at South Pole. In addition, at Summit, Greenland (72134 0 N, 38129 0 W, 3200 m elevation), the model of Yang et al (2002) predicted OH levels of more than 4 Â 10 6 molecules cm À3 .…”
Section: Introductionmentioning
confidence: 99%